'Breakthrough' political science: Multi-level governance – Reconceptualising Europe's modernised polity. (November 2020) - Jeffery, Charlie; Peterson, John
Multi-level governance has provoked debates over the last quarter century as the thinking of Liesbet Hooghe and Gary Marks has progressed. That thinking has been both innovative and eclectic, forming a number of intellectual 'story arcs' that part ways, develop and mature, then recombine with renewed force. We take Hooghe and Marks' Multi-Level Governance and European Integration as a pivotal moment in the development of that thinking. We then trace the 'story arcs' of multi-level governance by pinpointing three questions. Does multi-level governance 'travel' as a viable analytical framework much beyond cohesion policy? Does multi-level governance give analytical purchase beyond the European Union? And is multi-level governance merely a descriptive framework or does it embed or give rise to theory? We conclude by shortly summarising the contributions to this Breakthrough Political Science Symposium .